On the sustainability of paddy rice cultivation in the Paraíba do Sul river basin (Brazil) under a changing climate - Martins, Minella A.; Tomasella, Javier; Bassanelli, Hélio R. [UNESP]; Paiva, Ana Carolina E.; Vieira, Rita Márcia S.P.; Canamary, Erica A.; Alvarenga, Lívia A. (Elsevier, 2023)
Located in Southeast Brazil, the Paraíba do Sul River Basin is considered one of the most strategic in the country since it is the main source of fresh water for more than 14.3 million people. The population growth in recent decades, in combination with increased demand for water for industrial and agricultural activities, has generated concerns about how the combined effect of land uses and global climate change might affect water availability in the future. Once irrigation is one of the main water consumers, especially for paddy rice cultivation, in this study we used a crop simulation model to determine the water requirements of paddy rice under current and future climate conditions based on three different regionalized climate scenarios and for different land use and land cover change projections. In addition, we estimated water footprints for different irrigation and soil fertility strategies. Finally, we explored adaptation actions that can lead to more sustainable production. Projections indicate an increase in the productivity and efficiency of irrigated rice. Intermittent flooding proved to be an efficient alternative, rather than the traditional practice of continuous ponding. Most scenarios projected a gradual decrease in water footprint for rice cultivated using irrigation and soil fertility management. On the other hand, the water footprint under rainfed and non-optimum soil fertility resulted in higher water footprints. Due to changes in land use and land cover, mainly urban sprawl, the rice areas are expected to decrease in the future reducing the production in the region, which is expected to decrease by almost 10% in the period 2016–2035 and up to 38% in the period 2036–2055. This trend can be compensated by adopting sustainable practices in rice cultivation, such as rational soil fertility and water management, which can boost the current level of productivity by 50% and reduce water use by up to 15%.
Keywords: Crop modeling; Intermittent flooding; Water footprint